Unit Cost of Thai Traditional Medicine Service Activities for Health Promotion and Disease Prevention in Health Care Providers under Ministry of Public Health for the 2018 Fiscal Year - Singweratham, Noppcha; Khunboonchan, Thanida; Nawsuwan, Kittiporn; Atitdid, Praponpat (Princess of Naradhiwas University Journal, 2021)
This survey research aims to estimate the unit cost and calculate cost per capita of health promotion and disease prevention in Thai tradition medicine (TTM) activities in health care providers under Ministry of Public Health. The unit cost per activities were calculated based on activity-based costing (ABC) in the 2018 fiscal year and presented under providers’ perspective. The 8 provinces of TTM service prototype were purposive sampling in four regions. One community hospital and two health promoting hospitals in each province were selected. The secondary data was collected by empirical costing approach and normative costing approach. The unit cost and the cost per capita were presented with percentage and measures of central tendency. The findings showed the health care providers under Ministry of Public Health provided health promotion and disease prevention services in TTM for 5 age groups, about 98.08 percent of all TTM service activities for health promotion and diseases prevention. The labor cost was in the range of 54.51 – 82.73 percent. When compared with material and equipment costs, the range of median cost for 5 age groups was presented in Thai Bath (THB) as follows: 1) Pregnancy and after birth group with 11.03 – 206.56 THB, 2) Child with 0 – 5 age group with 15.47 – 25.27 THB, 3) 6 – 24 age group with 32.97 – 122.82, 4) Adult with 25 – 59 age group with 11.93 – 129.97 THB and 5) Elderly aged over 60 with 11.93 – 100.13 THB. In addition, the cost per capita was 465.43 THB for health promotion and disease prevention in TTM activities. The result of this study will support the policy recommendations for the benefit package relating to Thai Traditional Medicine Service Activities for Health Promotion and Disease Prevention.